Molecular Serotyping by Phylogenetic Analyses of a 1498bp Segment of the invA Gene of Salmonella - Windell L. Rivera; Rance Derrick Neri Pavon (ASM Science Journal, 2021)
The current gold standard for Salmonella serotyping is costly, labor-intensive and time-consuming. However, proper identification is key to monitor Salmonella transmission and implementation of necessary control measures. The onset of advanced molecular techniques has lessened resource and labor requirements; however, it still remains complex, unestablished and plagued with insufficiencies. Hence, a simpler serotyping method with sufficient resolution is needed. In this study, the invA virulence gene, associated with Salmonella invasion into host cells and is considered as a marker for Salmonella detection, was amplified and sequenced among isolates from meat samples in Metro Manila, Philippines. This was followed by sequence alignments with reference sequences (Refseqs), oversaturation and model tests, phylogenetic tree analyses and signal detections. Unfortunately, alignment of a 229bp amplified and sequenced invA gene segment with Refseqs generated little to no base variations and consequently provided insufficient phylogenetic resolution for molecular serotyping (0 of the 17 serotypes tested). However, another segment of 1498bp, outside the amplified region, showed considerable base variation in alignment and consequently resolved a maximum of 13 out of 17 (76.47%) serotypes tested, all generated trees considered. These suggest the potential of the invA virulence gene as a single-gene marker for molecular serotyping of Salmonella through phylogenetic analyses.